Digital CSR impact on Chinese auto brands: Mediating and moderating customer satisfaction and engagement - Manzar Rehman; Tong Zelin; Cun Wang; PuSheng Zhang; Talib Hussain; Muhammad Abdullah Khan; Farooq Ahmad Bajwa (Acta Psychologica, 2025)
Nowadays, Digital Corporate Social Responsibility (DCSR) affects a firm's performance by shaping much more than how people intend to buy the product or how loyal they are to the brand. This work helps fill a gap in the literature by studying how companies in the Chinese auto industry benefit from their reputations when it comes to brand valuation. Previous studies on CSR and consumer behavior largely ignore brand valuation as an important outcome and do not link their findings to a main theory. The study introduces Social Exchange Theory, Stakeholder Theory, and the Corporate Social Performance Model to the literature to design a well-structured framework. The analysis was based on 300 surveys of Chinese consumers from several automobile brands using SEM via AMOS to test the hypotheses. The research established that DCSR considerably raises a brand's valuation, which results from strong customer satisfaction and is affected by customer engagement as a moderating factor. It appears that combining digital CSR with a customer-focused approach in business strategy attracts customers and in the long run, benefits the brand. This study introduces useful information that helps plan and implement CSR strategies in the digital sphere. By offering a novel perspective on the synergistic relationship between digital CSR, customer satisfaction, and brand valuation within the competitive and dynamic realm of China's automobile sector, this paper makes a valuable contribution to the ongoing debate surrounding the strategic integration of CSR into business practices. It not only enriches the academic discussion on this subject but also provides actionable insights for practitioners aiming to leverage the power of CSR in the digital age, setting a precedent for future research and implementation in the domain.